2009
DOI: 10.1111/j.1365-2648.2009.05051.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with lower quality of life among patients receiving palliative care

Abstract: More could be done in symptom and psychosocial management to improve patients' QoL, in particular for those who are younger, male or single, or who have lower physical functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 53 publications
1
22
0
1
Order By: Relevance
“…Studies that include larger number of patients only tend to describe patients at the start of the palliative phase Jocham et al [2,5]. The period in which palliative care is provided to a patient however can last from a few months up to as much as 2 years Voogt et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that include larger number of patients only tend to describe patients at the start of the palliative phase Jocham et al [2,5]. The period in which palliative care is provided to a patient however can last from a few months up to as much as 2 years Voogt et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…3,4,13,15 To date, the literature concerning PCPs and PA shows promise, with beneficial improvements in QOL for adult PCPs. 3,5,[9][10][11]17,19,21,22 Although still in its infancy, researchers have found that adult PCPs who participate in a PA program gain feelings of increased energy, autonomy, and independence, and that PA can provide PCPs with situations where they can set goals and experience an environment of normalcy during a very challenging time.…”
Section: Discussionmentioning
confidence: 98%
“…4,9,10,15,17 In the not-too-distant past, patients with incurable malignancies were often discouraged from participating in PA. It was thought that these individuals needed to conserve their physical power; thus inactivity and rest were suggested as the most appropriate treatments.…”
Section: Palliative Care and Physical Activitymentioning
confidence: 99%
See 2 more Smart Citations